Three-Dimensional Ultrasound-Based Image-Guided Hypofractionated Radiotherapy for Intermediate-Risk Prostate Cancer: Results of a Consecutive Case Series. (7th February 2015) - Ricardi, Umberto; Franco, Pierfrancesco; Munoz, Fernando; Levis, Mario; Fiandra, Christian; Guarneri, Alessia; Moretto, Francesco; Bartoncini, Sara; Arcadipane, Francesca; Badellino, Serena; Piva, Cristina; Trino, Elisabetta; et al.
<x xml:space="preserve">Abstract</x> External beam radiotherapy (EBRT) is a standard of care in the treatment of prostate cancer. Hypofractionation is a valid option either radiobiologically and logistically in this context. Image-guidance procedures are strongly needed to provide ballistic precision to radiation delivery. The Clarity platform allows for the acquisition of three-dimensional ultrasound scans (3D-US) to perform image-guided radiotherapy. We treated a consecutive series of intermediate-risk prostate cancer patients (according to NCCN stratification) with a hypofractionated schedule (70.2 Gy/26 fractions at 2.7 Gy/daily to the prostate gland excluding the seminal vesicles at 62.1 Gy) under 3D-US guidance with the Clarity platform. The 3-year biochemical-relapse-free survival, distant-metastases-free, cancer-specific and overall survival were 98.6% (CI: 91.1–99.6%), 98.6% (CI: 91.1–99.6%), 97.5% (CI: 94.5–99.1%), and 94.3% (CI: 90.4–96.7%), respectively. Maximum detected acute GU toxicity was G0 in 22 patients (29.7%), G1 in 30 (22.7%), G2 in 19 (25.6%), G3 in 3 (4%). Maximum detected acute GI toxicity at the end of EBRT was G0 in 42 patients (56.8%), G1 in 22 (29.7%), G2 in 9 (12.1%), G3 in 1 (1.4%). The 3-year actuarial rates of ≥ G2 late toxicities were 6.1% for genito-urinary and 8.9% for gastrointestinal. The whole image-guidance workflow resulted in being robust and reliable. EBRT delivered employing a hypofractionated schedule under 3D-US-based image guidance proved to be a safe and effective treatment approach with consistent biochemical control and a mild toxicity profile. Hence, it has been transferred into daily clinical practice in our Department.